Design and Simulation of Screw Flow in a Prototype Injection Molding Machine Using Recycled Polypropylene - Riswan E. W. Susanto; Ahsin Fahmi M; Hafidzul Ulum; Rima Z. K. Nisak; Salim Subarkah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Plastic waste is currently still a serious problem for society due to the lack of sensitivity to environmental problems and the impact of careless disposal of plastic waste in many places. The injection molding process on industry scale often faces obstacles such as machines that have not worked efficiently, injection capacity that is unable to fill the mold completely, and the emergence of product defects due to plastic flow that begins to freeze before the entire cavity is completely filled. This study aims to design and simulate a prototype injection molding machine with a capacity of 4 tensile test specimens (total volume 28.5 cm³) in order to overcome these problems and to adjust the practicum needs of mechanical engineering students. The design process is carried out with SolidWorks software for 3D design, as well as flow simulation using SolidWorks Plastics and Flow Simulation with recycled Polypropylene (PP) material at melting temperature ± 230 ° C and injection pressure ± 5.3 MPa. The design results in a machine with dimensions of 1273 × 400 × 826 mm equipped with main components in the form of a frame, electric motor and gearbox, hopper, body safety, wheels, piston cylinder, control panel, heater, screw with barrel, and mold. SolidWorks Plastics simulation shows that the plastic flow fills the mold evenly with a filling time of 10.93 seconds, cycle time of 83.94 seconds, and maximum pressure of 5.38 MPa in the gate area, while Flow Simulation simulation shows a spiral flow pattern from the hopper to the end of the mold without backflow, with a mass flow rate of 0.0227 kg/sec and an average pressure of 97.765 Pa. These results prove that the design and simulation can improve process efficiency and mold quality